Perancangan Media Pembelajaran Pada Materi Alat Pernafasan Hewan dan Manusia Mata Pelajaran IPA SD Kelas V - Erik Oktavianus Allo; Adriyanto Juliastomo Gundo (Peneliti.net, 2021)
Teach and learn activities that still tend to be conventional causing many students to be less enthusiastic about listening to the materia, this causes the material presented is not maximally absorbed. The purpose of this study is to design learning media applications and then test the appropriateness of the application. It is expected that this application is feasible to be used to help the teaching and learning process. The focus of this application design is on natural science subjects, Animal and Human Respiratory materials. This research using the waterfall method in the application design. The research location is at Salatiga Public Elementary School 03. Respondents in this study are teachers and class V students. The results of the research diagram data obtained from student questionnaires and several teachers in every aspect fall into the